UNIVERSITY NOTES. (The Accounting Review, 1929)
This article presents news related to universities in the U.S., as of September 1929. W.H. Rowe, assistant professor of finance and accounting at University of Akron, is leaving the department to enter the Division of Finance of the Bureau of Agricultural Economics at Washington. W.F. Smith, certified public accountant of Upleger and Co., who has been a lecturer in the department at Baylor University, is resigning his position and D. Hudson, cashier of the university, will assume this work. Professor M.S. Carroll has been continuing his graduate study at the University of Chicago this summer. Students majoring in accounting have organized a society to promote further interest in the subject of accounting. Associate professor at University of California C.C. Staehling will be on sabbatical leave to complete work on a book on partnerships and their accounting problems. Lewis Lilly, certified public accountant at McLaren and Goode, will assume some of professor Staehling's work. L.O. Foster, instructor in accounting at University of Illinois, goes to Western Reserve University as assistant professor of economics to take charge of the work in accounting.